Effects of integrated models of care for diabetes and hypertension in low-income and middle-income countries: a systematic review and meta-analysis. Issue 7 (12th July 2021) - Rohwer, Anke; Uwimana Nicol, Jeannine; Toews, Ingrid; Young, Taryn; Bavuma, Charlotte M; Meerpohl, Joerg
Abstract : Objectives: To assess the effects of integrated models of care for people with multimorbidity including at least diabetes or hypertension in low-income and middle-income countries (LMICs) on health and process outcomes. Design: Systematic review. Data sources: We searched MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, LILACS, Africa-Wide, CINAHL and Web of Science up to 12 December 2019. Eligibility criteria: We included randomised controlled trials (RCTs), non-RCTs, controlled before-and-after studies and interrupted time series (ITS) studies of people with diabetes and/or hypertension plus any other disease, in LMICs; assessing the effects of integrated care. Data extraction and synthesis: Two authors independently screened retrieved records; extracted data and assessed risk of bias. We conducted meta-analysis where possible and assessed certainty of evidence using Grading of Recommendations Assessment, Development and Evaluation. Results: Of 7568 records, we included five studies—two ITS studies and three cluster RCTs. Studies were conducted in South Africa (n=3), Uganda/Kenya (n=1) and India (n=1). Integrated models of care compared with usual care may make little or no difference to mortality (very low certainty), the number of people achieving blood pressure (BP) or diabetes control (very low certainty) and access to care (very low certainty); may increase the number of people who achieve both HIV and BP/diabetes control (very low certainty); and may have a very small effect on achieving HIV control (very low certainty). Interventions to promote integrated delivery of care compared with usual care may make little or no difference to mortality (very low certainty), depression (very low certainty) and quality of life (very low certainty); and may have little or no effect on glycated haemoglobin (low certainty), systolic BP (low certainty) and total cholesterol levels (low certainty). Conclusions: Current evidence on the effects of integrated care on health outcomes is very uncertain. Programmes and policies on integrated care must consider context-specific factors related to health systems and populations. PROSPERO registration number: CRD42018099314.